2016
DOI: 10.1016/j.ultrasmedbio.2016.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Sonoreperfusion Therapy Kinetics in Whole Blood Using Ultrasound, Microbubbles and Tissue Plasminogen Activator

Abstract: Coronary intervention for myocardial infarction often results in microvascular embolization of thrombus. Sonoreperfusion therapy (SRP) using ultrasound and microbubbles restored perfusion in our in vitro flow model of microvascular obstruction. In this study, we assessed SRP efficacy using whole blood as the perfusate with and without tissue plasminogen activator (tPA). In a phantom vessel bearing a 40-μm pore mesh to simulate the microvasculature, microthrombi were injected to cause microvascular obstruction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…The efficacy of MB+US+tPA on sonoreperfusion using whole blood as the perfusate was previously reported by our group (Roos et al 2016). It is worth noting that in vivo homeostasis is hard to reproduce in vitro and our study did not recapitulate the complex dynamic process of thrombus formation-dissolution that occurs in hemostasis in vivo .…”
Section: Discussionsupporting
confidence: 70%
“…The efficacy of MB+US+tPA on sonoreperfusion using whole blood as the perfusate was previously reported by our group (Roos et al 2016). It is worth noting that in vivo homeostasis is hard to reproduce in vitro and our study did not recapitulate the complex dynamic process of thrombus formation-dissolution that occurs in hemostasis in vivo .…”
Section: Discussionsupporting
confidence: 70%
“…In a later study, using the same model, t-PA was added, resulting in an improvement of microvascular reperfusion. 36 Recently, Belcik et al confirmed these results in a hind limb ischemia mouse model using contrast ultrasound, and the authors observed that this improvement in microvascular flow lasted for more than 24 hours. 37 Even though the exact mechanism underlying this improvement in microvascular flow might not be known, a fair amount of studies with contrast ultrasound have been conducted in order to explore the effect on cellular level and thereby its potential beneficial effect on MVO.…”
Section: Pathophysiologymentioning
confidence: 84%
“…In a later study, using the same model, t-PA was added, resulting in an improvement of microvascular reperfusion. 36 Recently, Belcik et al confirmed these results in a hind limb ischemia mouse model using contrast ultrasound, and the authors observed that this improvement in microvascular flow lasted for more than 24 hours. 37…”
Section: Microvascular Obstructionmentioning
confidence: 84%
“…Studies suggest that ultrasonic radiation combined with drug-loaded microbubbles can dissolve thrombus directly by releasing drugs at the targeted sites, improving the effect of thrombolysis [58]. Ultrasound-enhanced thrombolysis is a promising strategy for the reperfusion therapies of acute stroke and other thrombus diseases [59, 60].…”
Section: Introductionmentioning
confidence: 99%